Breathless and Blue in the Canadian Longitudinal Study on Aging: Incident and Recurrent Depression Among Older Adults with COPD During the COVID-19 Pandemic - Taunque A; Li G; MacNeil A; Gulati I; Jiang Y; de Groh M; Fuller-Thomson E (International Journal of COPD, 2023)
Aneisha Taunque,1 Grace Li,2 Andie MacNeil,1,3 Ishnaa Gulati,4 Ying Jiang,5 Margaret de Groh,5 Esme Fuller-Thomson1,3,6,7 1Institute for Life Course and Aging, University of Toronto, Toronto, ON, Canada; 2Department of Sociology, University of Victoria, Victoria, BC, Canada; 3Factor-Inwentash Faculty of Social Work, University of Toronto, Toronto, ON, Canada; 4Dalla Lana School of Public Health, University of Toronto, Toronto, ON, Canada; 5Applied Research Division, Center for Surveillance and Applied Research, Public Health Agency of Canada, Ottawa, ON, Canada; 6Department of Family and Community Medicine, Temerty Faculty of Medicine, University of Toronto, Toronto, ON, Canada; 7Bloomberg Faculty of Nursing, University of Toronto, Toronto, ON, CanadaCorrespondence: Esme Fuller-Thomson, Institute for Life Course & Aging, Factor-Inwentash Faculty of Social Work, Cross-Appointed to Faculties of Medicine & Nursing, University of Toronto, 246 Bloor St. West, Toronto, ON, M5S 1V4, Canada, Tel +1 416 978-3269, Fax +1 416 978-7072, Email esme.fuller.Thomson@utoronto.caBackground and Objectives: The COVID-19 pandemic and related public health measures intensified risk factors for depression and concurrently heightened numerous health-related stressors for individuals with Chronic Obstructive Pulmonary Disease (COPD). Utilizing a comprehensive longitudinal sample of Canadian older adults, this study examined the incidence and recurrence of depression among older adults with COPD, and identified factors that were associated with depression during the pandemic among this population.Methods: Data came from four phases of the Canadian Longitudinal Study on Aging (CLSA) (n=875 with COPD). The primary outcome of interest was a positive screen for depression based on the CES-D-10, during autumn of 2020. Bivariate and multivariate logistic regression analyses were performed to identify factors that were associated with depression.Results: Approximately 1 in 6 (17%) respondents with COPD and no lifetime history of depression developed depression for the first time during the early stages of the pandemic. Approximately 1 in 2 (52%) participants with COPD and a history of depression experienced a recurrence of depressive symptoms during this period. Loneliness, functional limitations, and family conflict were associated with a higher risk of both incident and recurrent depression. The risk of incident depression only was higher among those who had difficulty accessing healthcare resources. The risk of recurrent depression only was higher among women, those with a post-secondary education, and those with more adverse childhood experiences.Conclusion: Screening and interventions aimed at individuals with COPD, both with and without a history of depression, are warranted to potentially mitigate the mental health impacts of the COVID-19 pandemic.Keywords: depression, older adults, COVID-19, CLSA